Application of Electronic tongue and HPLC in rapid determination of functional triterpenes and origins of Ganoderma lucidum - Tian, Jing; Wei, Jinfeng; Liu, Yuxin; Li, Changqin; Ma, Changyang; Kang, Wenyi (Frontiers in Nutrition, 2024)
In order to find rapid methods to evaluate the Ganoderma lucidum from different origins, Electronic tongue and High performance liquid chromatography (HPLC) were used in this paper. The Electronic tongue results combined with PCA and LDA analysis showed that the taste of different batches of G. lucidum from the same producing area was similar, but quite different from different producing areas. The overall taste of G. lucidum from Anhui was obviously different from that from Shandong and Sichuan. Meanwhile, the concentrations of two main triterpenes of G. lucidum, Ganoderic acid A and Ganoderic acid D were detected by using HPLC, and the variability of different origins were consistent with that from electronic tongue. Moreover, the triterpenoid acids content in G. lucidum from Shandong was about 1.04 mg/g, which is the highest of the three origins, followed by Sichuan and Anhui. Both the Electronic tongue and HPLC could efficiently distinguish the different origins of G. lucidum from taste property or content of key triterpenes, and provide new technical support for the quality evaluation of G. lucidum.